Gelatin coated TiO2-polypyrrole composite material as well as preparation method and application thereof

By preparing gelatin-covered TiO2-polypyrrole composite material, the problems of low lead adsorption efficiency and poor recovery performance in water treatment are solved, and efficient removal of lead ions and good regeneration in water bodies are achieved.

CN119608121AActive Publication Date: 2025-03-14GUANGZHOU KUANGRUI ENVIRONMENTAL TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411716815.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing nanotitanium dioxide materials face the problems of low lead adsorption efficiency and poor recovery performance in actual water treatment, which limits their application in large-scale water treatment.

Method used

By preparing gelatin-covered TiO2-polypyrrole composite material, the conductivity of polypyrrole and the high specific surface area of ​​nano-hydrated titanium dioxide are used, combined with the coating effect of gelatin, a synergistic adsorption network is formed, which improves the capture efficiency of lead ions.

Benefits of technology

The lead adsorption capacity and recovery performance of the composite material are significantly improved, and the efficient removal of lead ions in the water is achieved, with good regenerative and recyclable properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005157062000000011
    Figure HDA0005157062000000011
Patent Text Reader

Abstract

The invention belongs to the technical field of water purification materials, and particularly relates to a gelatin coated TiO2-polypyrrole composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: adding the polysorbate-80 into the paraffin oil, and stirring at 30-60 DEG C for 20-50 minutes to obtain an oil phase; heating water to 40-60 DEG C, then adding gelatin and the TiO2-polypyrrole composite precursor material, and stirring for 20-50 minutes to obtain a water phase; adding the water phase into the oil phase, and stirring for 30-60 minutes to obtain a mixed solution; and cooling the obtained mixed solution to 2-10 DEG C, then adding ethanol, stirring for 15-40 minutes, then sequentially washing with acetone and isopropanol, and freeze-drying the obtained solid matter, thereby obtaining the product. The polypyrrole and the gelatin contain functional groups such as amino groups, carboxyl groups and the like, and can form a complex with lead ions, so that the adsorption activity of the nano TiO2 material can be effectively improved, and the lead removal performance of the material is improved. The composite material disclosed by the invention shows very good removal rate and adsorption efficiency on lead ions in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water purification materials, and in particular to a gelatin-coated TiO2-polypyrrole composite material and a preparation method and application thereof. Background Art

[0002] Lead is a typical heavy metal with strong toxicity. Its main sources in the environment include the mining and smelting process of lead-containing mines and the industrial wastewater discharged by related enterprises. Especially in mining areas and industrially concentrated areas, the discharge of lead is high, causing serious pollution to water bodies. At the same time, the problem of lead pollution in tap water systems is becoming increasingly prominent. Although the water source has been purified, the use of lead-containing water pipes, joints and faucets may cause "secondary pollution" during transportation and storage, resulting in deterioration of water quality. The precipitation of lead in such piping systems may not only cause excessive lead content in the water body, but may also introduce bacteria and other harmful substances, posing a potential threat to public health. Lead poisoning has been proven to cause damage to the nervous system, cardiovascular system, and kidney function.

[0003] In order to cope with the increasingly serious lead pollution in water bodies, the development of efficient and stable lead removal materials has become a research hotspot in scientific research and industry. In recent years, nanomaterials have attracted widespread attention due to their unique physical and chemical properties. Among them, nano-titanium dioxide (TiO2) has shown good application prospects as a potential lead adsorbent. Nano-titanium dioxide has stable chemical properties, can remain active in acidic and alkaline environments, does not produce harmful byproducts, and has good photocatalytic properties, which helps to degrade organic pollutants in water. However, although nano-titanium dioxide has shown good ability to adsorb lead ions under laboratory conditions, its practical application still faces many challenges. First, the small size of nanoparticles makes it difficult to recover them from water after use, limiting their application in large-scale water treatment. In addition, although nano-titanium dioxide has a large specific surface area, its adsorption capacity is limited, and the lead removal efficiency needs to be improved urgently.

[0004] Therefore, there is an urgent need to develop modified nano-titanium dioxide composites to improve their lead adsorption capacity and recovery performance to ensure their effectiveness and operability in actual water treatment. Summary of the invention

[0005] According to a first aspect of the present invention, there is provided a method for preparing a gelatin-coated TiO2-polypyrrole composite material, comprising the following steps:

[0006] (1) adding pyrrole monomer to water, stirring evenly, then adding ammonium sulfate aqueous solution, stirring at 30-60° C. for 12-24 hours to obtain a polypyrrole solution; washing the polypyrrole solution, then adding nano-hydrated titanium dioxide to the washed polypyrrole solution, stirring at 30-50° C. for 5-10 hours to obtain a suspension, washing the suspension, drying, and grinding to obtain a TiO2-polypyrrole composite precursor material;

[0007] (2) adding polysorbate 80 to paraffin oil, stirring at 30-60° C. for 20-50 min to obtain an oil phase; heating water to 40-60° C., then adding gelatin and the TiO2-polypyrrole composite precursor material obtained in step (1), stirring for 20-50 min to obtain an aqueous phase; adding the aqueous phase to the oil phase, stirring for 30-60 min to obtain a mixed solution; cooling the obtained mixed solution to 2-10° C., then adding ethanol, stirring for 15-40 min, then washing with acetone and isopropanol in sequence, and freeze-drying the obtained solid to obtain the obtained product.

[0008] The method for preparing the gelatin-coated TiO2-polypyrrole composite material mainly includes chemical oxidation polymerization of polypyrrole, composite formation of TiO2 and polypyrrole and emulsification coating of gelatin.

[0009] The first step is chemical oxidation polymerization of polypyrrole: pyrrole monomer undergoes chemical oxidation polymerization under the action of oxidant ammonium sulfate to generate polypyrrole solution. Pyrrole monomer is oxidized to form free radical cations under the action of oxidant ammonium sulfate, and free radical cations further polymerize to form polypyrrole chains. The reaction is carried out in an aqueous phase at 30-60°C. The polypyrrole generated by oxidation polymerization has good conductivity and adsorption capacity.

[0010] The second step is the formation of TiO2-polypyrrole composite precursor material: adding nano-hydrated titanium dioxide to the washed polypyrrole solution and stirring evenly to form TiO2-polypyrrole composite precursor material. The functional groups in the polypyrrole molecules (such as amino and carbonyl groups) interact with the hydroxyl groups on the surface of TiO2 through hydrogen bonds or electrostatic interactions, so that the TiO2 particles are evenly distributed in the polypyrrole matrix. The conductive network structure of polypyrrole further enhances the electrochemical properties and adsorption capacity of the composite material.

[0011] Then comes the emulsification coating of gelatin: the TiO2-polypyrrole composite precursor material is dispersed in the gelatin solution, and the gelatin coating is achieved through an emulsification process. Gelatin is an amphiphilic molecule, and its amino and carboxyl groups can form chemical bonds or physical adsorption with the surfaces of TiO2 and polypyrrole, thereby forming a uniform gelatin coating layer on the surface of the composite material. The present invention uses polysorbate-80 (Span-80) and paraffin oil to form an oil phase, which is mixed with the aqueous phase to form a stable emulsified system, so that gelatin is uniformly deposited on the surface of the TiO2-polypyrrole particles. Then, the gelatin is further solidified by cooling and ethanol treatment to form a stable coating structure. Finally, acetone and isopropanol are used to wash to remove the emulsifier and residual substances to ensure the purity of the composite material.

[0012] In the gelatin-coated TiO2-polypyrrole composite material of the present invention, on the one hand, there is a synergistic effect between TiO2 and polypyrrole: TiO2 provides a large specific surface area and hydroxyl adsorption sites, while the nitrogen group of polypyrrole further supplements the adsorption sites to form a multifunctional adsorption network. At the same time, the conductive property of polypyrrole enhances the adsorption capacity of the composite material in an electrochemical environment, making the capture of heavy metal ions more efficient. On the other hand, there is a synergistic effect between the TiO2-polypyrrole composite precursor material and gelatin: gelatin improves the dispersibility of the composite particles by coating the TiO2-polypyrrole composite, avoiding agglomeration and affecting adsorption. Gelatin provides additional amino and carboxyl groups, increases the adsorption sites, and at the same time, through the amphiphilic function, the composite material maintains a high-efficiency adsorption capacity under different pH conditions. The coating of gelatin protects the composite material from environmental influences and extends the service life of the composite material.

[0013] In some embodiments, the preparation method of nano hydrated titanium dioxide comprises the following steps:

[0014] The titanium tetrachloride aqueous solution is stirred at 40-80°C for 10-30 minutes, and then the ammonia solution is added dropwise to the titanium tetrachloride aqueous solution. When the pH value reaches 8-10, the addition of the ammonia solution is stopped to obtain a white suspension. The white suspension is ultrasonically treated for 10-50 minutes, and then stirred at 50-80°C for 5-9 hours, and then centrifuged and washed to make its pH value 5-9; the hydrate obtained after washing is dried to a water content of 5-15wt%, and then ground for 30-60 minutes to obtain nano hydrated titanium dioxide.

[0015] When preparing nano-hydrated titanium dioxide, the present invention accurately controls the pH of the system to 8-10 by dripping ammonia water, thereby ensuring the complete precipitation of the TiO2 precursor (Ti(OH)4), while avoiding the generation of impurities or excessive agglomeration of particles due to excessively high pH. At the same time, ultrasonic treatment is performed after the white suspension is generated, which can effectively disperse the particles and break up large agglomerates, thereby ensuring the uniformity and nanometer size of the particles. The hydrate obtained after washing is dried to a water content of 5-15wt%, which can remove part of the bound water while avoiding complete dehydration, so that part of the bound water can be retained, forming a unique hydration state and improving the chemical activity of the material. At the same time, the porosity of the material is enhanced by mechanical grinding, and the particle uniformity and porous structure of the material are further improved, providing a higher specific surface area and more pores for subsequent adsorption and reaction.

[0016] The hydrated titanium dioxide prepared by the present invention through precise pH control and ultrasonic treatment has a high surface hydroxyl content, which provides more binding sites for subsequent compounding with polypyrrole and gelatin coating, and enhances synergistic performance. Ultrasonic treatment and mechanical grinding can effectively avoid particle agglomeration, ensure the uniformity of particle size distribution, and improve the dispersion performance and processing characteristics of the material. Through gentle stirring and drying processes, excessive grain growth is avoided, the porous structure is retained to the maximum extent, the specific surface area and pore volume of the material are increased, and the capture and adsorption performance of lead ions are improved. By controlling the water content of the hydrate to 5-15wt%, part of the bound water is retained, giving the material a higher chemical reaction activity, which helps to optimize the performance of the subsequent composite material. The preparation process adopts mild chemical and thermal treatment conditions, while avoiding the use of organic solvents, and has better environmental friendliness.

[0017] In some embodiments, the concentration of the titanium tetrachloride aqueous solution is 0.05-0.3 mol / L, and the volume fraction of the ammonia aqueous solution is 1-20%.

[0018] In some embodiments, the centrifugal speed is 4000-9000 r / min, each centrifugation is 3-5 minutes, and the centrifugation is performed 3-5 times.

[0019] In some embodiments, the hydrate obtained after washing is first dried at 50-80° C. for 4-8 h, and then dried at 90-120° C. to a water content of 5-15 wt %.

[0020] In some embodiments, in step (1), the volume ratio of pyrrole monomer to water is 1:(4-9).

[0021] In some embodiments, in step (1), the concentration of the aqueous ammonium sulfate solution is 0.5-2 mol / L, and the ratio of the sum of the volumes of the pyrrole monomer and water to the volume of the aqueous ammonium sulfate solution is 100:(20-80).

[0022] In some embodiments, in step (1), the ratio of the mass of nano-hydrated titanium dioxide to the volume of the washed polypyrrole solution is (5-10):100.

[0023] In some embodiments, in step (2), the volume ratio of polysorbate 80 to paraffin oil is (3-6):200.

[0024] In some embodiments, in step (2), the mass ratio of gelatin to the TiO2-polypyrrole composite precursor material is 1:(0.5-1.5), and the ratio of the sum of the masses of gelatin and the TiO2-polypyrrole composite precursor material to the volume of water is (1.5-2.5):10.

[0025] In some embodiments, in step (2), the volume ratio of ethanol to the mixed solution is (50-90):214.

[0026] In some embodiments, in step (2), the freeze-drying temperature is -80 to -40°C and the time is 10 to 20 hours.

[0027] According to a second aspect of the present invention, there is provided a gelatin-coated TiO2-polypyrrole composite material prepared by the above preparation method.

[0028] According to a third aspect of the present invention, there is provided a use of the gelatin-coated TiO2-polypyrrole composite material in the preparation of a lead ion adsorption passivation material.

[0029] The beneficial effects of the present invention include:

[0030] (1) The gelatin-coated TiO2-polypyrrole composite material of the present invention is based on anatase / amorphous nano-hydrated titanium dioxide, and these nanoparticles are very small and have high surface energy. Polypyrrole provides good conductivity and chemical stability, and at the same time, the complexing ability with lead ions is enhanced through the functional groups such as amino and carboxyl in its structure. Gelatin, as a natural polymer, has good biocompatibility and environmental protection, which can reduce the negative impact of the material on the environment. At the same time, the addition of gelatin provides additional functionality to the composite material and improves the mechanical strength and stability of the material. The gelatin-coated TiO2-polypyrrole composite material of the present invention achieves a good coating effect through polymerization reaction and cross-linking curing, ensuring the synergistic effect of each component. Polypyrrole and gelatin contain functional groups such as amino and carboxyl, which can form complexes with lead ions, effectively improve the adsorption activity of nano-TiO2, and enhance the lead removal performance of the material.

[0031] (2) The preparation method of the gelatin-coated TiO2-polypyrrole composite material of the present invention is simple, the prepared composite material has good regeneration and recyclability, shows very good removal rate and adsorption efficiency for lead ions in water, and has higher economic benefits in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a curve diagram of the lead ion removal rate of each test sample changing with time. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the accompanying drawings. It is worth noting that the following examples are only for better explanation of the content of the present invention and are not intended to limit the scope of protection of the present invention. The undisclosed process steps in the examples are prior art. Unless otherwise specified, the following raw materials are commercially available.

[0034] Example 1

[0035] The preparation method of the gelatin-coated TiO2-polypyrrole composite material of this embodiment comprises the following steps:

[0036] (1) Stir 1L of 0.1mol / L titanium tetrachloride aqueous solution at 60°C for 20min at a speed of 500rpm, then uniformly add a 5% ammonia solution to the titanium tetrachloride aqueous solution. When the pH value reaches 9.0, stop adding the ammonia solution to obtain a white suspension. Ultrasonicate the white suspension for 30min, then magnetically stir at 60°C at 600rpm for 6h. Then centrifuge the suspension with deionized water as a dispersion liquid at a speed of 5000r / min, centrifuge for 4min each time, centrifuge 4 times, and make its pH value 7.0. Dry the hydrate obtained after washing at 60°C for 4h, then dry at 100°C to a water content of about 10wt%, and then mechanically grind for 40min to obtain amorphous mixed nano-hydrated titanium dioxide.

[0037] (2) Add 10 mL of pyrrole monomer to 90 mL of deionized water, stir evenly, then slowly add 50 mL of 1 mol / L ammonium sulfate aqueous solution, stir magnetically at 50°C for 12 hours, and rotate at 800 rpm to make the pyrrole monomer undergo polymerization reaction to obtain a polypyrrole solution. Then, use deionized water as a dispersion liquid to fully wash the above polypyrrole solution to obtain 100 mL of polypyrrole precursor solution. Add 8 g of nano-hydrated titanium dioxide obtained in step (1) to the above polypyrrole precursor solution, stir at a constant temperature of 40°C for 6 hours to fully coat it, and obtain a suspension. Then, wash the obtained suspension by suction filtration, and then dry at a constant temperature of 50°C for 6 hours, and fully grind to obtain a TiO2-polypyrrole composite precursor material.

[0038] (3) Add 4 mL of polysorbate-80 to 200 mL of paraffin oil, stir magnetically at 50°C for 30 min at a speed of 600 rpm to obtain an oil phase. Heat 10 mL of deionized water to 50°C, add 1 g of gelatin and 0.8 g of the TiO2-polypyrrole composite precursor obtained in step (2), and stir for 30 min to obtain an aqueous phase. Add the above aqueous phase to the above oil phase and stir for 30 min to obtain a mixed solution. Cool the obtained mixed solution to 4°C with an ice water bath, then add 75 mL of ethanol and stir for 30 min, then wash with acetone and isopropanol seven times in sequence, and freeze-dry the obtained solid at -50°C for 20 h to obtain a gelatin-coated TiO2-polypyrrole composite material.

[0039] Comparative Example 1

[0040] The preparation method of the composite material of this comparative example is basically the same as that of Example 1, except that the polypyrrole modification treatment is not added in this comparative example. Specifically, the preparation method comprises the following steps:

[0041] (1) Stir 1L of 0.1mol / L titanium tetrachloride aqueous solution at 60°C for 20min at a speed of 500rpm, then uniformly add a 5% ammonia solution to the titanium tetrachloride aqueous solution. When the pH value reaches 9.0, stop adding the ammonia solution to obtain a white suspension. Ultrasonicate the white suspension for 30min, then magnetically stir at 60°C at 600rpm for 6h. Then centrifuge the suspension with deionized water as a dispersion liquid at a speed of 5000r / min, centrifuge for 4min each time, centrifuge 4 times, and make its pH value 7.0. Dry the hydrate obtained after washing at 60°C for 4h, then dry at 100°C to a water content of about 10wt%, and then mechanically grind for 40min to obtain amorphous mixed nano-hydrated titanium dioxide.

[0042] (2) Add 4 mL of polysorbate-80 to 200 mL of paraffin oil, stir magnetically at 50° C. for 30 min at a speed of 600 rpm to obtain an oil phase. Heat 10 mL of deionized water to 50° C., add 1 g of gelatin and 0.8 g of nano-hydrated titanium dioxide obtained in step (1), and stir for 30 min to obtain an aqueous phase. Add the aqueous phase to the oil phase and stir for 30 min to obtain a mixed solution. Cool the obtained mixed solution to 4° C. with an ice-water bath, then add 75 mL of ethanol and stir for 30 min, then wash with acetone and isopropanol seven times in sequence, and freeze-dry the obtained solid at -50° C. for 20 h to obtain the obtained solid.

[0043] Comparative Example 2

[0044] The preparation method of the composite material of this comparative example is basically the same as that of Example 1, except that gelatin coating treatment is not added in this comparative example. Specifically, the preparation method comprises the following steps:

[0045] (1) Stir 1L of 0.1mol / L titanium tetrachloride aqueous solution at 60°C for 20min at a speed of 500rpm, then uniformly add a 5% ammonia solution to the titanium tetrachloride aqueous solution. When the pH value reaches 9.0, stop adding the ammonia solution to obtain a white suspension. Ultrasonicate the white suspension for 30min, then magnetically stir at 60°C at 600rpm for 6h. Then centrifuge the suspension with deionized water as a dispersion liquid at a speed of 5000r / min, centrifuge for 4min each time, centrifuge 4 times, and make its pH value 7.0. Dry the hydrate obtained after washing at 60°C for 4h, then dry at 100°C to a water content of about 10wt%, and then mechanically grind for 40min to obtain amorphous mixed nano-hydrated titanium dioxide.

[0046] (2) Add 10 mL of pyrrole monomer to 90 mL of deionized water, stir evenly, then slowly add 50 mL of 1 mol / L ammonium sulfate aqueous solution, stir magnetically at 50°C for 12 hours, and rotate at 800 rpm to make the pyrrole monomer undergo polymerization reaction to obtain a polypyrrole solution. Then, use deionized water as a dispersion liquid to fully wash the above polypyrrole solution to obtain 100 mL of polypyrrole precursor solution. Add 8 g of nano-hydrated titanium dioxide obtained in step (1) to the above polypyrrole precursor solution, stir at a constant temperature of 40°C for 6 hours to fully coat it, and obtain a suspension. Then, wash the obtained suspension by suction filtration, and then dry at a constant temperature of 50°C for 6 hours, and fully grind to obtain a TiO2-polypyrrole composite precursor material.

[0047] (3) Add 4 mL of polysorbate-80 to 200 mL of paraffin oil, stir magnetically at 50 ° C for 30 minutes at a speed of 600 rpm to obtain an oil phase. Heat 10 mL of deionized water to 50 ° C, add 0.8 g of the TiO2-polypyrrole composite precursor material obtained in step (2), and stir for 30 minutes to obtain an aqueous phase. Add the above aqueous phase to the above oil phase and stir for 30 minutes to obtain a mixed solution. Cool the obtained mixed solution to 4 ° C with an ice water bath, then add 75 mL of ethanol and stir for 30 minutes, then wash with acetone and isopropanol seven times in sequence, and freeze-dry the obtained solid at -50 ° C for 20 hours.

[0048] Next, in order to verify the adsorption capacity of the gelatin-coated TiO2-polypyrrole composite material prepared by the present invention on lead ions in wastewater, a lead ion adsorption test was carried out on the composite materials prepared in Example 1 and Comparative Examples 1-2.

[0049] 1. Test subjects

[0050] The gelatin-coated TiO2-polypyrrole composite material prepared in Example 1 and the composite material prepared in Comparative Examples 1-2.

[0051] 2. Test methods

[0052] Taking industrial wastewater as the waste liquid to be treated, the concentration of lead ions in the waste liquid to be treated was detected by inductively coupled plasma mass spectrometry and was 0.16 mg / L.

[0053] Take 0.1g of the test sample and place it in 100mL of the waste liquid to be treated, adjust the pH to 8.5, and stir at 300r / min at room temperature for 20, 40, and 60min respectively. After solid-liquid separation, detect the concentration of lead ions in the solution, calculate the lead ion removal rate and make a record. Test each sample 3 times and take the average value. Lead ion removal rate (%) = (c i -c f ) / c i × 100%, where c i is the initial concentration of lead ions, in mg / L; c f It is the concentration of lead ions after adsorption, in mg / L.

[0054] 3. Test results

[0055] The change curve of lead ion removal rate of each test sample over time is as follows: Figure 1 The lead ion removal rate of each test sample after 60 minutes of adsorption is shown in Table 1.

[0056] Table 1 Lead ion removal rate of each test sample after 60 minutes of adsorption

[0057] Example 1 Comparative Example 1 Comparative Example 2 Lead ion removal rate / % 99.4 92.3 90.3

[0058] From Table 1 and Figure 1 It can be seen from the results that the adsorption rate of the test sample is the fastest within 0-20 minutes, and then the adsorption rate gradually slows down, reaching the maximum adsorption capacity in 60 minutes. The lead ion removal rate of the gelatin-coated TiO2-polypyrrole composite material for industrial wastewater prepared in Example 1 is 99.4%, close to 100%, showing very excellent lead ion adsorption performance; while the lead ion removal rate of the composite material of Comparative Examples 1-2 for industrial wastewater is only about 90%. It can be seen that the gelatin-coated TiO2-polypyrrole composite material of the present invention has a stronger adsorption capacity for lead ions in industrial wastewater than the composite material without polypyrrole modification or gelatin coating.

[0059] The above are only some specific embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a gelatin-coated TiO2-polypyrrole composite material, characterized in that: The steps include: (1) adding pyrrole monomer to water, stirring evenly, then adding ammonium sulfate aqueous solution, stirring at 30-60° C. for 12-24 hours to obtain a polypyrrole solution; washing the polypyrrole solution, then adding nano-hydrated titanium dioxide to the washed polypyrrole solution, stirring at 30-50° C. for 5-10 hours to obtain a suspension, washing the suspension, drying, and grinding to obtain a TiO2-polypyrrole composite precursor material; (2) adding polysorbate 80 to paraffin oil, stirring at 30-60° C. for 20-50 min to obtain an oil phase; heating water to 40-60° C., then adding gelatin and the TiO2-polypyrrole composite precursor material obtained in step (1), stirring for 20-50 min to obtain an aqueous phase; adding the aqueous phase to the oil phase, stirring for 30-60 min to obtain a mixed solution; cooling the obtained mixed solution to 2-10° C., then adding ethanol, stirring for 15-40 min, then washing with acetone and isopropanol in sequence, and freeze-drying the obtained solid to obtain the obtained product.

2. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 1, characterized in that: The preparation method of the nano hydrated titanium dioxide comprises the following steps: The titanium tetrachloride aqueous solution is stirred at 40-80°C for 10-30 minutes, and then the ammonia solution is added dropwise to the titanium tetrachloride aqueous solution. When the pH value reaches 8-10, the addition of the ammonia solution is stopped to obtain a white suspension. The white suspension is ultrasonically treated for 10-50 minutes, and then stirred at 50-80°C for 5-9 hours, and then centrifuged and washed to make its pH value 5-9; the hydrate obtained after washing is dried to a water content of 5-15wt%, and then ground for 30-60 minutes to obtain nano hydrated titanium dioxide.

3. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 2, characterized in that: The concentration of the titanium tetrachloride aqueous solution is 0.05-0.3 mol / L, and the volume fraction of the ammonia aqueous solution is 1-20%.

4. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 2 or 3, characterized in that: The centrifugal speed is 4000-9000r / min, each centrifugation is 3-5min, and the centrifugation is 3-5 times; The hydrate obtained after washing is first dried at 50-80° C. for 4-8 h, and then dried at 90-120° C. to a water content of 5-15 wt %.

5. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 1 or 2, characterized in that: In step (1), the volume ratio of the pyrrole monomer to water is 1:(4-9); The concentration of the ammonium sulfate aqueous solution is 0.5-2 mol / L, and the ratio of the sum of the volumes of the pyrrole monomer and water to the volume of the ammonium sulfate aqueous solution is 100:(20-80); The ratio of the mass of the nano-hydrated titanium dioxide to the volume of the washed polypyrrole solution is (5-10):

100.

6. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 1 or 2, characterized in that: In step (2), the volume ratio of polysorbate 80 to paraffin oil is (3-6):200; The mass ratio of gelatin to the TiO2-polypyrrole composite precursor material is 1:(0.5-1.5), and the volume ratio of the sum of the mass of gelatin and the TiO2-polypyrrole composite precursor material to water is (1.5-2.5):10; The volume ratio of the ethanol to the mixed solution is (50-90):

214.

7. The method for preparing the gelatin-coated TiO2-polypyrrole composite material according to claim 1 or 2, characterized in that: In step (2), the freeze-drying temperature is -80 to -40°C and the time is 10 to 20 hours.

8. The gelatin-coated TiO2-polypyrrole composite material obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the gelatin-coated TiO2-polypyrrole composite material according to claim 8 in the preparation of lead ion adsorption passivation materials.

Citation Information

Patent Citations

  • Polypyrrole / titanium dioxide composite adsorbent, its preparation, application and regeneration methods

    CN102350317A

  • Composite adsorbent, membrane protective agent and water treatment agent

    CN110605102A

  • Gelatin-based hydrogel adsorbent for adsorbing hexavalent chromium ions and preparation method of gelatin-based hydrogel adsorbent

    CN112169780A

  • Composite activated carbon and conductive polymer adsorption media

    WO2018014052A1